Konfigurasi fraktur Schatzker VI dan malalignment merupakan faktor risiko terjadinya joint narrowing pada fraktur tibia plateau di RSUP Sanglah, Bali, Indonesia - Herryanto Agustriadi Simanjuntak; Ketut Siki Kawiyana; I Ketut Suyasa; Putu Astawa; Ketut Gede Mulyadi Ridia; I Wayan Suryanto Dusak; I Gede Eka Wiratnaya; I Wayan Subawa (Intisari Sains Medis, 2020)
Background: Tibia plateau fracture is a fracture that involves the joint surface and dramatically contributes to the early development of knee osteoarthritis, which can lead to disability. The joint narrowing is one of the most initial signs of knee osteoarthritis. Until now, the mechanism of joint narrowing is not known with certainty but is thought to be related to the configuration of the patient's fracture, malalignment, and BMI. This study aims to determine and analyze the effect of Schatzker VI fracture configuration, malalignment, and BMI > 25 kg/m2 on joint narrowing in post-operative tibia plateau fracture patients.Methods: This research is an observational study with a case-control design. Thirty-eight patients with tibia plateau fractures who had surgery with acceptable reduction were followed-up within 12-15 months post-operatively. The control group consisted of patients who did not experience joint narrowing post-operatively, while the case group are patients with joint narrowing. Schatzker classification, malalignment, and BMI were compared and statistically analyzed for significance. Data were analyzed using SPSS version 21 for Windows.Results: Sixteen patients (84,0%) had Schatzker VI with a risk of 11.56 times to experience joint narrowing (p=0.003). Malalignment were 18 samples (47,0%), with a risk of 11,56 times becoming joint narrowing (p=0.003); and 8 samples with BMI > 25 kg/m2 had a risk of 0.802 times to develop joint narrowing (p=1.000).Conclusion: Schatzker VI configuration and malalignment are risk factors for joint narrowing in patients following tibial plateau surgery, while a BMI is not a risk factor for joint narrowing. Latar Belakang: Fraktur tibia plateau merupakan fraktur yang melibatkan permukaan sendi dan sangat berkontribusi terhadap perkembangan dini osteoartritis lutut yang dapat berujung pada timbulnya disabilitas. Joint narrowing merupakan salah satu tanda awal terjadinya osteoartritis lutut. Sampai saat ini mekanisme terjadinya joint narrowing belum diketahui secara pasti namun diduga terkait dengan konfigurasi fraktur, malalignment, dan BMI pasien. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh konfigurasi fraktur Schatzker VI, malalignment, dan BMI > 25 kg/m2 terhadap terjadinya joint narrowing pada pasien pasca operasi fraktur tibia plateau.Metode: Penelitian ini merupakan studi observasional dengan desain case control. Tiga puluh delapan pasien yang menjalani operasi fraktur tibia plateau diamati dalam 12-15 bulan pasca operasi. Kelompok kontrol terdiri dari pasien yang tidak mengalami joint narrowing pasca operasi sedangkan kelompok kasus terdiri dari pasien yang mengalami joint narrowing. Klasifikasi Schatzker, malalignment, dan BMI dibandingkan dan dianalisis secara statistik untuk signifikansi.Hasil: Enam belas pasien (84,0%) memiliki konfigurasi fraktur Schatzker VI berisiko 11,56 kali mengalami joint narrowing (p=0,003); malalignment dengan 18 sampel (47%), berisiko 11,56 kali menjadi joint narrowing (p=0,003); dan sampel dengan BMI> 25 kg/m2 adalah 8 sampel dan berisiko 0,802 kali untuk mengalami joint narrowing (p=1.000). Simpulan: Konfigurasi Schatzker VI fraktur tibia plateau dan malalignment adalah faktor risiko untuk terjadinya joint narrowing pada pasien yang pasca operasi fraktur tibia plateau, sementara BMI > 25kg/m2 bukan merupakan faktor risiko terjadinya joint narrowing.